Effects of Cooling Interventions with Different Target Temperatures on Heat Stroke Rats - Wu C; Wang P; Wang B; Nijiati M; Hou M (Dove Medical Press, 2023)
Changdong Wu,* Ping Wang,* Bin Wang, Muyesai Nijiati, Ming Hou Xinjiang Emergency Center, People's Hospital of Xinjiang Uygur Autonomous Region, Urumqi, 830001, People's Republic of China*These authors contributed equally to this workCorrespondence: Ming Hou, Xinjiang Emergency Center, People's Hospital of Xinjiang Uygur Autonomous Region, No. 91, Tian-chi Road, Tianshan District, Urumqi, 830001, People's Republic of China, Tel +86-9918563596, Email houming199@sina.comPurpose: To investigate the optimal target temperature of cooling intervention in heat stroke (HS) rats and explore the potential mechanisms of cooling intervention in alleviating heat stroke-induced damage.Materials and Methods: A total of 32 Sprague-Dawley rats were randomly divided into 4 groups (n=8/group), including control, HS[core body temperature (Tc)], HS(Tc-1°C) and HS(Tc+1°C) group. Heat stroke model was established in rats of HS(Tc), HS(Tc-1°C) and HS(Tc+1°C) group. Rats in HS(Tc) group were cooled to baseline core body temperature after establishing heat stroke model, HS(Tc-1°C) group to baseline core body temperature minus 1°C and HS(Tc+1°C) group to baseline core body temperature plus 1°C. We compared the histopathological changes of lung, liver and renal tissue, as well as cell apoptosis and expression of critical proteins in phosphatidylinositol 3´-kinase (PI3K)/Akt signaling pathway.Results: Heat stroke caused the histopathological damage and cell apoptosis of lung, liver and renal tissue, which could be alleviated by cooling intervention to a certain extent. Notably, HS(Tc+1°C) group demonstrated a better effect on alleviating cell apoptosis although the differences were not significant. Heat stroke lead to the elevated expression of p-Akt, which subsequently induced the elevated expression of Caspase-3 and Bax, as well as the decreased expression of Bcl-2. Cooling intervention could reverse this trend. Notably, the expression level of Bax in lung tissue of HS(Tc+1°C) group was significantly lower than that of HS(Tc) and HS(Tc-1°C) group.Conclusion: The mechanisms of cooling intervention in alleviating heat stroke-induced damage were associated with the expression changes of p-Akt, Caspase-3, Bax and Bcl-2. The better effect of Tc+1°C might be associated with low expression of Bax.Keywords: heat stroke, cooling intervention, target temperature, histopathological damage, cell apoptosis, PI3K/Akt signaling pathway